LEXICAL CHOICE AND STYLISTICS DEVICES (Наука и инновации, 2026)
This article investigates the role of lexical choice in text stylistics and its stylistic effectiveness. It thoroughly analyzes the significance of the word selection process in shaping the semantic and emotional load of discourse. The authors illustrate, with examples, the stylistic differentiation of lexical units used in various contexts and their impact on the reader or listener. The research findings demonstrate the crucial role of lexical choice in determining the overall tone, genre, and communicative purpose of a text. This article offers valuable insights for specialists in linguistics, stylistics, and text studies.